2013
DOI: 10.1177/0888406413502734
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of E-Mentoring on Beginning Teacher Competencies and Perceptions

Abstract: There is a critical need to mentor novice special education teachers to meet the current and projected teacher shortages. However, due to the various skill-levels of beginning special education teachers in schools and the small number of current special educators in each school who could serve as mentors, there is difficulty finding induction-level mentors that possess similar or the same teaching credentials or teaching assignments as mentees in the same schools or geographical regions. Electronic mentoring (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 16 publications
1
19
0
2
Order By: Relevance
“…Students commented that: to hear perspectives from different cultures … the distance may actual [sic] promote closeness in the relationships with peers in a way that may not happen with day-to-day work colleagues -you can be honest in saying some things (potentially critical of your own school) that you might be reticent to share with those teaching in the same school. (Participant 1, narrative) These indings support the argument that an online mentoring and educational programme can be beneicial to the learner and their careers (Gutke and Albion, 2008;Hunt et al, 2013), especially for a course designed to encourage the development of a globally mobile teacher, where cultural competence and exposure to a range of opinions and perspectives is beneicial to the ever-changing work environment (Hacohen, 2012). The opportunity to personalize the programme according to development needs was highlighted as a strength among all participants, showing that the diverse learning needs of teachers in intercultural contexts must be met with equally diverse and intercultural training solutions.…”
Section: Requirements Of Teacher Education and Development In The Glosupporting
confidence: 59%
“…Students commented that: to hear perspectives from different cultures … the distance may actual [sic] promote closeness in the relationships with peers in a way that may not happen with day-to-day work colleagues -you can be honest in saying some things (potentially critical of your own school) that you might be reticent to share with those teaching in the same school. (Participant 1, narrative) These indings support the argument that an online mentoring and educational programme can be beneicial to the learner and their careers (Gutke and Albion, 2008;Hunt et al, 2013), especially for a course designed to encourage the development of a globally mobile teacher, where cultural competence and exposure to a range of opinions and perspectives is beneicial to the ever-changing work environment (Hacohen, 2012). The opportunity to personalize the programme according to development needs was highlighted as a strength among all participants, showing that the diverse learning needs of teachers in intercultural contexts must be met with equally diverse and intercultural training solutions.…”
Section: Requirements Of Teacher Education and Development In The Glosupporting
confidence: 59%
“…Effects of induction and mentoring on instructional quality and effectiveness. Teachers who participate in induction and mentoring report feeling more competent (Hunt, Powell, Little, & Mike, 2013;Mathur, Gerhke, & Kim, 2013), and there is some evidence that comprehensive induction can contribute to teacher effectiveness (Glazerman et al, 2010;Ingersoll & Strong, 2011). Ingersoll and Strong's review found that, across studies, new teachers who participated in comprehensive induction used stronger instructional prac tices and were more effective in promoting student achieve ment.…”
Section: Effects Of Induction and Mentoring On Retentionmentioning
confidence: 99%
“…In addition to often serving more than one school (Schmidt, Gage, Gage, Cox, & McLeskey, 2015), rural special education teachers may have the challenge of addressing the needs of families who reside in poverty with fewer resources and less access to information (Meadan, Halle, & Eata, 2010), present cultural and linguistic challenges (Marshall, Kirby, & Gorski, 2016), feel discomfort interacting with professional educators due to lack of education or other hardships (Thurston & Navarrete, 2010), or have child care or transportation issues that preclude their involvement (Conroy, 2012). If working in multiple schools, rural special education teachers may have the challenge of proximity in trying to collaborate with and mentor general education teachers (Hunt, Powell, Little, & Mike, 2013). Finally, although there is evidence that rural schools may be more inclusive than urban schools (Brock & Schafer, 2015), rural special education teachers may need to work with school administrators to establish guidelines for communication and best practices.…”
Section: Rural Special Education Teachers As Leaders At the School Levelmentioning
confidence: 99%
“…A successful mentoring program (e.g., Childre & Van Rie, 2015) will identify the participant, address needed professional development, access needed resources, have consistent meeting times, document goals, and celebrate achievements. It is possible that teachers in some rural schools may not be in close proximity to a certified special education teacher (Hunt et al, 2013). Instead of traveling to schools to mentor new teachers, synchronous technologies provide the opportunity to observe special education teachers and provide real-time feedback and coaching from a distance (Billingsley, Israel, & Smith, 2011;Ploessl & Rock, 2015;Rock et al, 2014;Scheeler, McKinnon, & Stout, 2012;Schmidt et al, 2015).…”
Section: Mentoringmentioning
confidence: 99%